2014
DOI: 10.1016/j.jaci.2014.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Maternal allergy increases susceptibility to offspring allergy in association with TH2-biased epigenetic alterations in a mouse model of peanut allergy

Abstract: Background Although maternal atopy is a risk factor for development of peanut allergy, this phenomenon has not been well-characterized experimentally, and the mechanisms underlying offspring risk are unclear. Objective To determine if offspring of peanut allergic mothers (O-PAM) are more susceptible to peanut allergy than offspring of naive mothers (O-NM) in a murine model; and if so whether the susceptibility is linked to Th2 biased epigenetic alterations. Methods Five-week-old O-PAM and O-NM were intraga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Epigenetic mechanisms have been implicated in allergic responses [17,27]. Maternal peanut allergy was associated with hypomethylation at CpG -408 and CpG -393 of the IL-4 promoter in splenocytes and mesenteric lymph node cells in offspring compared to offspring of naïve mice [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epigenetic mechanisms have been implicated in allergic responses [17,27]. Maternal peanut allergy was associated with hypomethylation at CpG -408 and CpG -393 of the IL-4 promoter in splenocytes and mesenteric lymph node cells in offspring compared to offspring of naïve mice [17].…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic mechanisms have been implicated in allergic responses [17,27]. Maternal peanut allergy was associated with hypomethylation at CpG -408 and CpG -393 of the IL-4 promoter in splenocytes and mesenteric lymph node cells in offspring compared to offspring of naïve mice [17]. Similarly, in an asthma mouse model, antigen plus diesel exposure induced hypomethylation at CpG -408 of the IL-4 promoter, and the degree of methylation at CpG -408 correlated inversely with IgE levels [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown that antenatal particulate exposure in mice resulted in distinct methylation changes and increased susceptibility to allergic airway diseases in up to three subsequent offspring generations [92, 93]. In a murine model of peanut allergy, offspring of peanut-sensitized mothers were more susceptible to the development of peanut allergy, through epigenetic alterations of the IL-4 gene promoter [94]. …”
Section: Second-generation International Immigrantsmentioning
confidence: 99%
“…Song et al [21] conducted an animal (mouse) study in order to examine the relationship of allergy susceptibility and Th2-biased epigenetic alterations. The offspring of mothers with peanut allergy and the offspring of naive mothers were both sensitized with peanut.…”
Section: Interleukinsmentioning
confidence: 99%